2019
DOI: 10.1186/s12890-019-0924-5
|View full text |Cite
|
Sign up to set email alerts
|

Serial ultrasound assessment of diaphragmatic function and clinical outcome in patients with amyotrophic lateral sclerosis

Abstract: Background Diaphragmatic assessment by ultrasound (US) is a non-invasive and useful method in the clinical management of patients with Amyotrophic Lateral Sclerosis (ALS). The aim of our observational study was to evaluate the impact of serial assessment of the diaphragmatic function by US on long-term outcomes in a series of patients suffering from ALS and to correlate US indices of diaphragmatic function and respiratory function tests with these outcomes. Methods A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Lastly, the ratio between diaphragm thickness at the end of tidal volume and the diaphragm thickness at maximal inspiration (ΔTmax) has been proposed by Fantini et al ( 16 ) to detect impairment in pulmonary function tests and as an indication for mechanical ventilation support in patients suffering from ALS. Indeed, the ΔTmax has been related to respiratory function tests ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the ratio between diaphragm thickness at the end of tidal volume and the diaphragm thickness at maximal inspiration (ΔTmax) has been proposed by Fantini et al ( 16 ) to detect impairment in pulmonary function tests and as an indication for mechanical ventilation support in patients suffering from ALS. Indeed, the ΔTmax has been related to respiratory function tests ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following this, diaphragmatic dysfunction was documented by histopathology or ultrasonography in case reports of single patients with sporadic IBM 6,7 . The usefulness of ultrasonography to help quantify diaphragm function has already been described in other neuromuscular diseases such as amyotrophic lateral sclerosis (ALS), Duchenne muscular dystrophy, and Pompe disease, 8‐11 and has been validated in the evaluation of isolated unilateral diaphragm paralysis and in the intensive care unit setting 12‐20 …”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that the measurement of diaphragmatic mobility could be a reliable tool to identify impaired respiratory function (FVC < 50% of predicted) in patients with ALS or myotonic dystrophy. In a more recent study, Fantini et al 88 found that, in patients with ALS, a Tdi at V T /Tdi at TLC ratio > 0.75 (suggesting diaphragmatic weakness) increased the risk of requiring NIV (hazard ratio = 5.6; p = 0.001) and the risk of death (hazard ratio = 3.7; p = 0.0001), inferring that diaphragmatic ultrasound is an accurate method of predicting the need for NIV in ALS.…”
Section: Neuromuscular Diseasesmentioning
confidence: 93%
“…Maximal excursion correlated with FVC 87 4. The Tdi at V T /Tdi at TLC ratio is indicative of weakness and may predict NIV initiation in ALS 88 5. Duchenne muscular dystrophy and myotonic dystrophy type 1: Reduced mobility during DB and VS 89 DB excursion correlated with FVC values 89 Diaphragm thickness and excursion are reduced and correlate with lung function in ALS.…”
Section: Diaphragmatic Ultrasound In Respiratory Diseasesmentioning
confidence: 99%